2006
DOI: 10.1002/macp.200600201
|View full text |Cite
|
Sign up to set email alerts
|

New Siloxane‐Organic Polyesters with Azobenzene Side Chains. Synthesis, Thermotropic Behavior and Surface Properties

Abstract: Summary: New siloxane‐organic polyesters, bearing azo‐type units in the side chain, were synthesized by direct solution polycondensation at room temperature, starting from 2,2′‐[4‐[(4‐nitrophenyl)azo]phenyl]iminobisethanol (Disperse Red 19) and different siloxane diacids, using dicyclohexylcarbodiimide as an activator and 4‐(N,N‐dimethylamino)pyridinium‐p‐toluenesulfonate as the catalyst. The structure of the obtained polyesters was confirmed by 1H and 13C NMR as well as IR spectroscopy. The molecular weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Synthesis of monoazo‐diol 4‐[bis(2‐hydroxyethyl)amino]‐4′‐acetylazobenzene was carried out in a two‐step procedure: diazotization of 4‐acetylaniline followed by coupling with N , N ‐bis(β‐hydroxyethyl)aniline, melting point 159–160 °C. 1 H NMR (DMSO‐d 6 ): δ 2.6 ppm − CH 3 −CO−; δ 3.6 ppm –CH 2 −; δ 4.8 ppm –OH; δ 6.9 aromatic protons ortho to –N<; δ 7.8 aromatic protons ortho to –N = N−; δ 8.1 aromatic protons ortho to –COCH 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of monoazo‐diol 4‐[bis(2‐hydroxyethyl)amino]‐4′‐acetylazobenzene was carried out in a two‐step procedure: diazotization of 4‐acetylaniline followed by coupling with N , N ‐bis(β‐hydroxyethyl)aniline, melting point 159–160 °C. 1 H NMR (DMSO‐d 6 ): δ 2.6 ppm − CH 3 −CO−; δ 3.6 ppm –CH 2 −; δ 4.8 ppm –OH; δ 6.9 aromatic protons ortho to –N<; δ 7.8 aromatic protons ortho to –N = N−; δ 8.1 aromatic protons ortho to –COCH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have been focused on the design and development of new polymers with photodegradable and biodegradable properties. Polymers containing azobenzene units are extensively studied because of their large potential applications: optical data storage, liquid crystal displays, surface relief gratings . These polymers have unique photochemical and thermal isomerization properties which depend on polymeric architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report a synchronized polymerization and self-assembly (SPSA) strategy for synthesizing highly uniform and shape-anisotropic polymer NPs with uniaxial internal molecular orientation by using a monomer that consists of a rigid rod-like 4-nitroazobenzene (NAB) and a flexible spacer (–(CH 2 ) n –) through dispersion polymerization. Similar monomers have been used to form liquid crystalline polymers. We demonstrate that such monomers can be used to synthesize uniform polymer NPs with well-defined cylindrical shapes and a single-domain lamella LC structure. The formation mechanism suggested that a short nucleation period, the completion of microphase separation before glassification, at which localized microphase separation is frozen, and sufficient low particle/solvent interfacial tension are the origins of highly uniform dimensions, single liquid crystal domains, and well-defined shapes of particles.…”
Section: Introductionmentioning
confidence: 93%
“…Among the polymers used as biomaterials, homopolyesters and copolyesters were found to be attractive due to the diversity of available monomers and of polymerization procedures allowing fine tuning of their physical and chemical properties 16. In fact, the strategies applied for the synthesis of azobenzene functional polymers considered the attachment of photosensitive moieties to short chain oligoesters that are subsequently incorporated in linear17 or dendritic18 block copolymers. The synthesis of novel azofunctional oligoesters19 was previously performed through ring‐opening oligomerization of cyclic esters like ε‐caprolactone (ε‐CL) and D, L ‐lactide.…”
Section: Introductionmentioning
confidence: 99%